2017
DOI: 10.1515/logos-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Middle Jurassic–Early Cretaceous foraminiferal biozonation of the Amran Group, eastern Sana’a Basin, Yemen

Abstract: Two sections of strata assigned to the Amran Group at Jabal Salab and Jabal Yam in the eastern Sana’a governorate were sampled and correlated. These sections are part of a carbonate platform that extends from the city of Marib in the east to Naqil Ibn Ghailan, 20 km east of the city of Sana’a to the west. Palaeontological analysis of samples recovered has resulted in identification of 123 foraminiferal species, which are used to subdivide the sequence of the Amran Group into five biostratigraphic zones, aged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Abu-Zeid et al [2] reported that these raw materials exist in the Jurassic Amran Group (Shuqra, Madbi, Nayfa and Sab'atayn formations), the Cretaceous Tawilah sandstone, the Tertiary Trap Series, the Quaternary Yemen and Aden Volcanics and the Quaternary wadi deposits as well as some in the Precambrian Basement rocks (Table 1). The stratigraphy and tectonic setting of these rock units have been studied by several researchers [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Abu-Zeid et al [2] reported that these raw materials exist in the Jurassic Amran Group (Shuqra, Madbi, Nayfa and Sab'atayn formations), the Cretaceous Tawilah sandstone, the Tertiary Trap Series, the Quaternary Yemen and Aden Volcanics and the Quaternary wadi deposits as well as some in the Precambrian Basement rocks (Table 1). The stratigraphy and tectonic setting of these rock units have been studied by several researchers [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%